Francisco Marcos de Velasco and the Art of Flanders: Library, Paintings, Tapestries and Funerary Chapel (BSAA arte, 2019)
Francisco Marcos de Velasco, member of a secondary branch of the Velasco family, made his military career together with the Constable of Castile, Íñigo Melchor Fernández de Velasco. He ended up being Governor of the Antwerp fortress and Marquis of Pico de Velasco. He was in contact with David Teniers III and he owned numerous works of art from Flanders. His testators built one of the most sumptuous chapels of that period. It was decorated with an altar and a funerary monument made by Pieter Scheemaeckers. His tomb is preserved in a chapel of St James church in Antwerp. In addition, we study his library and his paintings and tapestries.
Keywords: Francisco Marcos de Velasco; Marquis of Pico de Velasco; Pieter Scheemaeckers; Baroque sculpture; Flanders; Antwerp